2011
DOI: 10.1051/0004-6361/201016319
|View full text |Cite
|
Sign up to set email alerts
|

Long period variables and mass loss in the globular clusters NGC 362 and NGC 2808

Abstract: Context. The pulsation periods of long period variables (LPVs) depend on their mass and helium abundance as well as on their luminosity and metal abundance. Comparison of the observed periods of LPVs in globular clusters with models is capable of revealing the amount of mass lost on the giant branch and the helium abundance. Aims. We aim to determine the amount of mass loss that has occurred on the giant branches of the low metallicity globular clusters NGC 362 and NGC 2808. We also aim to see if the LPVs in N… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 68 publications
2
16
0
Order By: Relevance
“…Studies have shown that the amplitudes of Mira pulsations do not exceed 30 km s −1 (e.g. Hinkle 1978;Hinkle et al 1982;Hinkle et al 1997;Lebzelter et al 2000;Lebzelter et al 2005;Lebzelter & Wood 2011). Our stars show velocities faster than this limit.…”
Section: Atmospheric Active Starsmentioning
confidence: 67%
See 1 more Smart Citation
“…Studies have shown that the amplitudes of Mira pulsations do not exceed 30 km s −1 (e.g. Hinkle 1978;Hinkle et al 1982;Hinkle et al 1997;Lebzelter et al 2000;Lebzelter et al 2005;Lebzelter & Wood 2011). Our stars show velocities faster than this limit.…”
Section: Atmospheric Active Starsmentioning
confidence: 67%
“…However, an explanation could be that these stars have radial velocities of about 20 km s −1 on top of their Mira pulsations. Lebzelter & Wood (2011) recently investigated the long period variables of NGC 2808. Unfortunately, they had to exclude the inner regions of the cluster due to crowding.…”
Section: Atmospheric Active Starsmentioning
confidence: 99%
“…This effect is most noticeable in spectral features such as the TiO bands which are predominantly formed in the coolest, brightest giants. We were able to trace a one percent difference between our two R7000 observations of NGC 2808 (observed 159 days apart) to three known (Lebzelter & Wood 2011) long period variables in our field-of-view.…”
Section: Fe5335 Fe5270mentioning
confidence: 82%
“…Most of the mass loss occurs on the AGB, except for the lower-mass stars where mass loss on the RGB is substantial in a relative sense, of the order 0.25 M in total (McDonald et al 2009(McDonald et al , 2011Lebzelter and Wood 2011).…”
Section: The Total Mass Lost By An Agb Starmentioning
confidence: 99%